Case Report: Late-Onset Lennox-Gastaut Syndrome Treated With Stereotactic Electroencephalography-Guided Radiofrequency Thermocoagulation Before Craniotomy - Li, Sixian; Cai, Xiaodong; Yao, Chen; Wang, Yuanqing; Xiao, Xiaohua; Yang, Huafeng; Yao, Yi; Chen, Lei (Frontiers in Neurology, 2022)
Abstract The onset of Lennox-Gastaut Syndrome (LGS), a severe epilepsy syndrome, is typically before 8 years of age. Late-onset LGS (with onset in adolescence and adulthood) is relatively rare clinically and has some differences from classical LGS. Herein, we describe the case of a patient with late-onset LGS and provide a literature review of such cases. The patient had focal epilepsy onset at 8 years of age. After a 9-year evolution, he suffered seizures of different types and met the diagnosis of late-onset LGS. Drug treatment was ineffective. Nothing was found on stereotactic electroencephalography (SEEG) and magnetic resonance imaging (MRI) during the disease course. After a second presurgical evaluation, a suspicious focus was on high-resolution structural MRI, verified by SEEG. After SEEG-guided radiofrequency thermocoagulation (RFTC), his seizures were controlled, and his cognitive function and quality of living clearly improved. However, his seizures recurred 2 years later, and he underwent left occipital resection. Thereafter, his seizures have been controlled until now. This case emphasizes the importance of high-resolution structural MRI in the treatment of LGS. Furthermore, it suggests that late-onset LGS may be caused by focal lesions and evolve from focal epilepsy. Thus, characterizing the clinical symptoms and performing individualized electroencephalographic follow up are both very important. Additionally, the clinical outcome in the present case implies the value and limitations of RFTC in patients with epilepsy with a clear focal lesion. Moreover, the present case further supports differences between late-onset and classical LGS in terms of the clinical manifestation, cognitive changes, prognosis, and treatment.